Dharmaśāstra and social awareness - Jha, V. N. (Sri Satguru Publications, 1996)
Contributed research papers presented at the National Seminar on "Dharmaśāstra and Social Awareness", held at the Centre of Advanced Study in Sanskrit, University of Poona, 1994.